Effect of Danshen for improving clinical outcomes in patients with bladder cancer: a retrospective, population-based study - Yi-Hsin Chen; Yi-Hsin Chen; Yi-Hsin Chen; Chih-Tsung Chen; Han-Ping Wu; Han-Ping Wu (Frontiers Media S.A., 2023)
Introduction: Traditional Chinese Medicine (TCM) has a broad application in healthcare, with Danshen being a notable herb used in Eastern medicine for cancer treatment. This study aims to explore the relationship between Danshen use and cardiovascular risks among bladder cancer patients.Methods: Patients were selected based on a confirmed diagnosis of bladder cancer with specific inclusion and exclusion criteria to control for certain comorbidities and treatments. Utilizing Taiwan's National Health Insurance data from 2003 to 2013, this retrospective, population-based study identified three groups: 525 patients treated with Danshen, 6,419 patients not treated with TCM, and 4,356 patients treated with TCM but not with Danshen. The Cox proportional hazard model was employed to estimate the risks of Major Adverse Cardiovascular Events (MACE) and mortality while accounting for various confounders.Results: The overall incidence of MACEs was significantly lower in the Danshen group (5%) compared to the TCM (8.1%) and non-TCM (9.9%) groups (p < 0.001). The Cox model revealed that bladder cancer patients treated with Danshen had the lowest risk of MACE (adjusted hazard ratio, 0.56; 95% confidence interval, 0.38-0.84) and all-cause mortality (adjusted hazard ratio, 0.60; 95% confidence interval, 0.44-0.82).Discussion: The findings suggest that Danshen reduces the risk of MACE and all-cause mortality in bladder cancer patients, highlighting its potential benefits. This underpins the necessity for further research to substantiate the cardiovascular benefits of Danshen in bladder cancer patients and potentially broaden its application in oncology healthcare.